End-condition for solution small angle X-ray scattering measurements by kernel density estimation. Issue 1 (31st December 2022) - Sekiguchi, Hiroshi; Ohta, Noboru; Ishibashi, Hideaki; Hino, Hideitsu; Mizumaki, Masaichiro
ABSTRACT: We develop a method for calculating the minimum X-ray exposure time for X-ray solution scattering experiments using statistical and mathematical approaches to enhance the measurement efficiency while maintaining data quality. Experts can determine the X-ray exposure time for samples by investigating time-series data of scattering profiles and considering the quality of scattering profiles and the samples' X-ray damage. In this study, we apply a statistical inequality to estimate the kernel density estimation method's error to determine the minimum X-ray exposure time for protein solution scattering experiments and evaluate the method's validity using the results of Guinier analysis as an indicator. GRAPHICAL ABSTRACT: uf0001